Cadaveric study validating in vitro monitoring techniques to measure the failure mechanism of glenoid implants against clinical CT - Junaid,S; Gregory,T; Fetherston,S; Emery,R; Amis,AA; Hansen,U (Journal of Orthopaedic Research, 2018)
Definite glenoid implant loosening is identifiable on radiographs, however, identifying early loosening still eludes clinicians. Methods to monitor glenoid loosening in vitro have not been validated to clinical imaging. This study investigates the correlation between in vitro measures and CT images. Ten cadaveric scapulae were implanted with a pegged glenoid implant and fatigue tested to failure. Each scapulae were cyclically loaded superiorly and CT scanned every 20,000 cycles until failure to monitor progressive radiolucent lines. Superior and inferior rim displacements were also measured. A finite element (FE) model of one scapula was used to analyze the interfacial stresses at the implant/cement and cement/bone interfaces. All ten implants failed inferiorly at the implant-cement interface, two also failed at the cement-bone interface inferiorly, and three showed superior failure. Failure occurred at of 80,966 ± 53,729 (mean ± SD) cycles. CT scans confirmed failure of the fixation, and in most cases, was observed either before or with visual failure. Significant correlations were found between inferior rim displacement, vertical head displacement and failure of the glenoid implant. The FE model showed peak tensile stresses inferiorly and high compressive stresses superiorly, corroborating experimental findings. In vitro monitoring methods correlated to failure progression in clinical CT images possibly indicating its capacity to detect loosening earlier for earlier clinical intervention if needed. Its use in detecting failure non-destructively for implant development and testing is also valuable. The study highlights failure at the implant-cement interface and early signs of failure are identifiable in CT images. © 2018 The Authors. Journal of Orthopaedic Research® Published by Wiley Periodicals, Inc. on behalf of the Orthopaedic Research Society. J Orthop Res 9999:XX-XX, 2018.